All regimes mobility extraction using split C–V technique enhanced with charge-sheet model. (September 2015) - Hubert, Q.; Carmona, M.; Rebuffat, B.; Innocenti, J.; Masson, P.; Masoero, L.; Julien, F.; Lopez, L.; Chiquet, P.
Highlights: Split C – V method is paired with charge-sheet model to extract effective mobility. Effective mobility is extracted from weak to strong inversion. Effective mobility is extracted from ohmic regime to saturation regime. A non-zero and V DS independent effective mobility is observed in weak inversion. Effective mobility extracted is modeled using simple empirical models. Abstract: In this paper, carrier effective mobility is accurately extracted from weak to strong inversion and from ohmic to saturation regimes by pairing the split C – V technique with charge-sheet model. In weak inversion, both electron and hole effective mobility are found to be constant and V DS independent. Moreover, effective mobility extracted by this new method is modeled in all regimes using already published models extended up to the saturation regime.